Preparation, spectroscopic characterization of a new cd(ii) complex containing tridentate nno schiff base derived and x-ray crystallographic structural study of 3,4,5 trihydroxybenzoic acid[1-(pyridyl)-ethylidene]hydrazone - Alhadi, A.A.; Shaker, S.A.; Gwaram, N.S.; Yehye, W.A.; Ali, Hapipah Mohd (Sociedad Chilena de Química, 2012)
A new Cd(II) complex with a tridentate Schiff base derivative which was obtained from condensation of gallic hydrazid with 2-acetylpyridine has been prepared. The structure of the ligand 3,4,5-Trihydroxybenzoic acid[1-(pyridyl)-ethylidene]hydrazone (GAPy) was confirmed using the X-ray structure analysis. The elemental analysis, FTIR, UV-Vis, 1H NMR spectral and Thermal analysis indicates that the Schiff base ligand GAPy is a tridentate ligand which is coordinated with the Cd(II) complex through N,N and O atoms. Thus, the acetate ion is a bidentate ligand that is coordinated with the metal ion through two O atoms.